Heat transfer enhancement in nucleate boiling on micropillar-arrayed surfaces with time-varying wettability. (5th January 2022) - Chen, Hong-Xia; Li, Lin-Han; Wang, Yi-Ran; Guo, Yu-Xiang
Highlights: A conceptual design of textured surfaces with time-varying wettability is proposed. The design increases the bubble departure frequency and suppresses dry spots. The design enhances interface evaporation but deteriorates microlayer evaporation. The heat transfer rate is enhanced by 38.5% as compared with constant wettability. Abstract: Microstructured surfaces with spatial arrangements of hydrophilic and hydrophobic regions have been widely studied in boiling heat transfer enhancement. In this study, a conceptual design of microstructured surfaces with time-varying wettability is proposed to regulate bubble dynamics and thus enhance the heat transfer performance in the nucleate boiling regime. The effectiveness of the design is examined numerically for single-bubble heat transfer on a micropillar-arrayed silicon surface using a comprehensive three-dimensional model. The intrinsic contact angle is initially set as 48°, it is subsequently reduced to 20° in the bubble growth (0.152 and 0.4 ms) or departure stage (0.60 and 0.80 ms). The simulations show that two mechanisms contribute to heat transfer enhancement. First, the time-varying wettability decreases the adhesion force on the bubble exerted by the surface, thereby increasing the bubble departure frequency. Second, it also increases the local curvatures of the bubble, leading to the formation of thin liquid films between the bubble and micropillar walls. The liquid films suppress dry spots and hence enhance the heat removal of the bubble from the surface. The simulations also show that the reduction in the intrinsic contact angle enhances the evaporation on the liquid–vapor interface but deteriorates the evaporation in the microlayer. Because the former dominates the heat transfer process of the bubble on the micropillar-arrayed surface, the time-varying wettability increases the total evaporation rate. In the meantime, the time-varying wettability reduces the time proportion of the departure stage, which shortens the weakened heat transfer period in a bubble life-cycle and thus enhances the average heat transfer rate. As compared the case with constant wettability, the average heat transfer rate for the cases with time-varying wettability increases by 38.5%, 23.1%, 19.2%, and 15.4%, respectively, when the intrinsic contact angle is reduced at 0.152, 0.40, 0.60, and 0.80 ms, indicating that earlier wettability modulation gives rise to more significant heat transfer enhancement. The optimal time for wettability modulation is exactly the same as the time at which the total evaporation rate begins to decline.